The Contribution of of the Karya Bhakti Mandiri Cooperative for development of native chicken livestock business in the Bengalon district East Kutai Regency (Jurnal Pertanian Terpadu, 2020)
This study aims were to analyze the contribution of the KBM Cooperative for development of native chicken livestock business in the Bengalon district East Kutai Regency. The study was conducted in June-August 2019. Explanatory research was used to explain the causal relationship between role variables and business development through testing hypotheses Chi Square test and Spearman Correlation. The contribution of the KBM was calculated from the coefficient of determination. Sampling of active cooperative member respondents were 50 people with questionnaire instruments that had been tested for validity and reliability. The role of the KBM Cooperative had an average of 52% or in the medium category, the development of chicken farming by KBM cooperatives was on average 60% in the high category. There was relationship between the role of the KBM Cooperative on the development of native chicken livestock business the result of Chi Square test χ2 count = 31.290 compared to χ2 table (α = 0.05) = 9.488, Relationship was in the strong category (rs = 0.748). The contribution of KBM was 55% contributed for development of native chicken livestock business in the Bengalon districtKeyword: Contribution, Cooperative, Chi Square, Spearman Correlation, SPSS
Keywords: Contribution; Cooperative; Chi Square; Spearman Correlation; SPSS